Combination of an electrochemical pretreatment with a biological oxidation for the mineralization of nonbiodegradable organic dyes: Basic yellow 28 dye. Issue 1 (28th March 2013) - Yahiaoui, Idris; Aissani‐Benissad, Farida; Fourcade, Florence; Amrane, Abdeltif
<x xml:space="preserve">Abstract</x> The aim of this article was to examine the feasibility of combining an electrochemical degradation of wastewater containing Basic Yellow 28 (BY28) dye on Pb/PbO2 electrode and a biological treatment. A central composite design (CCD) was used for the screening of the significant operating parameters and the identification of the most relevant interactions. The model equation obtained led to a classification of these parameters based on their level of significance, namely temperature followed by the initial concentration of BY28, the current density and the agitation speed. A significant interaction occurred between the temperature and the initial dye concentration. The second‐order model obtained by CCD led to the following optimal conditions for dye degradation: 50 ≤ T ≤ 60°C, 8.125 ≤ i ≤ 25 mA cm−2, [BY28]0 = 134 mg L−1, and ω = 720 rpm. Under these conditions, the obtained BY28 dye degradation yield was 96%. The (BOD5/COD) ratio increased from 0.076 initially to 0.30 after pretreatment, showing that the electrochemical pretreatment of BY28 dye generate intermediate products, which are at least partially biodegradable. Microbial degradation was therefore performed for the pretreated solution in an aerobic batch reactor for 30 days using an activated sludge culture. A decrease of the residual amount of intermediate products contained in the electrolyzed solutions was observed which can be related to a biological oxidation, leading to 93% removal of the dissolved organic carbon by the combined process. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 160–169, 2014